The interaction between SDS and lysozyme at the hydrophilic solid-water interface - Green, R; Su, T; Lu, JR; Penfold, J (2001)
The interaction between sodium dodecyl sulfate (SDS) and preadsorbed lysozyme at the hydrophilic silicon oxide-water interface has been studied using specular neutron reflection. Measurements were carried out using two different solution concentrations of lysozyme and a range of SDS solution concentrations between 0.2 and 2 mM. The surface composition and the adsorbed layer structure were determined by varying H/D labeling of SDS. Initially, a uniform layer or bilayer of protein was formed at the interface by adsorption from either 0.03 or 1 g/L lysozyme solution concentrations. The SDS was then added to the system and the neutron reflectivity measured. It was found that this method of studying the SDS/lysozyme system produced highly repeatable neutron reflectivity profiles. On addition of intermediate SDS concentrations, cooperative binding of the SDS to the protein layer was observed, without any evidence of removal of the preadsorbed protein layer. On increasing the SDS concentration, to above 0.5 mM SDS, partial removal of the protein layer occurred. A concentration of 2 mM SDS was required to completely remove all traces of adsorbed material from the interface. These results suggest that the mechanism for protein elution from the interface is via the coadsorption of SDS to the protein layer and the formation of a SDS/protein complex whose surface activity varies with the extent of SDS binding. © 2001 American Chemical Society.